Colour pattern studies: the SE (せ) method, a shape-centred approach to explore biodiversity and avoid aesthetic biases - Pierre Galipot (Quantitative Plant Biology)
The preference towards colourful patterns generates many aesthetic biases, including in Biology research, leading to taxonomic preferences and understudied groups, including many plant taxa. After reviewing the importance of aesthetics in Turing colour pattern studies and the relative nature of the sense of beauty in Biology, I present a method called SE (せ) that strongly reduces taxonomic preferences in colour pattern formation studies, together with allowing the exploration of colour patterns biodiversity and facilitating the discovery of new morphogenesis processes.